Do Tax Strategies and Political Ties Shape Sustainability? - Wardhana, Ricko Syahputra Jaya; Putri, Sofie Yunida (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2026)
This study analyzes the effect of tax aggressiveness and political connections on corporate sustainability, with firm size as a moderating variable, using 27 State-Owned Enterprises (SOEs) and Local Government-Owned Enterprises (LGOEs) listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Employing a quantitative approach with panel data regression, tax aggressiveness is measured through CETR, political connections through board affiliation indicators, firm size through total assets, and corporate sustainability through ESG-related disclosure scores. The results show that tax aggressiveness has no significant effect on corporate sustainability, indicating that short-term tax-reduction strategies do not translate into improvements in long-term sustainability performance. In contrast, political connections demonstrate a positive and significant influence on corporate sustainability. This suggests that politically connected firms may gain better access to resources, stronger institutional support, and enhanced legitimacy, thereby improving their sustainability outcomes. Furthermore, firm size does not moderate the relationship between tax aggressiveness and corporate sustainability, nor does it moderate the effect of political connections. This implies that the benefits of political ties persist regardless of organizational scale, and the impact of tax aggressiveness remains consistent across both smaller and larger SOEs/LGOEs. In practice, these findings highlight the importance of state-owned enterprises in strengthening governance structures while leveraging political relationships constructively to enhance sustainability performance. Building transparent collaborations and aligning political support with long-term sustainability goals can help SOEs and LGOEs improve their resilience and public accountability.